Effect of dapagliflozin on ventricular arrhythmias, resuscitated cardiac arrest, or sudden death in DAPA-HF. (27th August 2021) - Curtain, James P; Docherty, Kieran F; Jhund, Pardeep S; Petrie, Mark C; Inzucchi, Silvio E; Køber, Lars; Kosiborod, Mikhail N; Martinez, Felipe A; Ponikowski, Piotr; Sabatine, Marc S; Bengtsson, Olof; Langkilde, Anna Maria; et al.
Abstract: Aims: The aim of this study was to examine the effect of dapagliflozin on the incidence of ventricular arrhythmias and sudden death in patients with heart failure and reduced ejection fraction (HFrEF). Methods and results: In a post hoc analysis of DAPA-HF, we examined serious adverse event reports related to ventricular arrhythmias or cardiac arrest, in addition to adjudicated sudden death. The effect of dapagliflozin, compared with placebo, on the composite of the first occurrence of any serious ventricular arrhythmia, resuscitated cardiac arrest, or sudden death was examined using Cox proportional hazards models. A serious ventricular arrhythmia was reported in 115 (2.4%) of the 4744 patients in DAPA-HF (ventricular fibrillation in 15 patients, ventricular tachycardia in 86, 'other' ventricular arrhythmia/tachyarrhythmia in 12, and torsade de pointes in 2 patients). A total of 206 (41%) of the 500 cardiovascular deaths occurred suddenly. Eight patients survived resuscitation from cardiac arrest. Independent predictors of the composite outcome (first occurrence of any serious ventricular arrhythmia, resuscitated cardiac arrest or sudden death), ranked by chi-square value, were log-transformed N-terminal pro-B-type natriuretic peptide, history of ventricular arrhythmia, left ventricular ejection fraction, systolic blood pressure, history of myocardial infarction, male sex, body mass index, serum sodium concentration, non-white race, treatment with dapagliflozin, and cardiac resynchronization therapy. Of participants assigned to dapagliflozin, 140/2373 patients (5.9%) experienced the composite outcome compared with 175/2371 patients (7.4%) in the placebo group [hazard ratio 0.79 (95% confidence interval 0.63–0.99), P  = 0.037], and the effect was consistent across each of the components of the composite outcome. Conclusions: Dapagliflozin reduced the risk of any serious ventricular arrhythmia, cardiac arrest, or sudden death when added to conventional therapy in patients with HFrEF. Clinical trial registration:  ClinicalTrials.gov unique identifier: NCT03036124 (DAPA-HF). Graphical Abstract: